Lightweight Cf/HC–SiBCN composite for multifunctional applications - Lingyu Yang; Lumeng Wang; Shun Dong; Guiqing Chen; Changqing Hong; Xinghong Zhang; Yanchun Zhou (Journal of Advanced Ceramics, 2025)
Carbon fiber composites hold significant promise as electromagnetic wave (EMW)-absorbing materials. However, balancing lightweight materials with excellent mechanical properties, low thermal conductivity, and EMW absorption for multifunctional applications remains challenging. Herein, a novel hydrothermal carbon (HC)-coated three-dimensional (3D) needled carbon fiber-reinforced silicon–boron carbonitride (Cf/HC–SiBCN) composite was developed via an optimized precursor infiltration and pyrolysis (PIP) process combined with impregnation–filtration. By adjusting the precursor concentration and number of impregnation‒filtration cycles, a hierarchical Cf/HC–SiBCN composite with the density of 0.32 g·cm−3 was obtained, which exhibited remarkable mechanical properties, including flexural strengths of 14.75±0.43 MPa (xy-direction) and 14.45±0.66 MPa (z-direction), along with a compressive strength of 9.36±0.20 MPa (z-direction). It also demonstrated low thermal conductivity (0.145 W·m−1·K−1) and exceptional EMW absorption, with a minimum reflection loss (RLmin) of −58.13 dB and an effective absorption bandwidth (EAB) of 7.38 GHz. Owing to their combination of lightweight, enhanced mechanical properties, low thermal conductivity, and superior EMW absorption capabilities, Cf/HC–SiBCN composites are highly suitable for multifunctional applications.